PENGEMBANGAN FITUR REKOGNISI KEGIATAN DENGAN METODE SCRUM - Nurmasani, Atik; Setiawan, Annas; Hartanto, Anggit Dwi (Universitas Amikom Yogyakarta, 2024)
Activity recognition from independent activities can be done according to learning outcomes. The recognition process uses Google form with submission stages, checking stages, and decision-making stages. The problems at checking stage are the conversion calculation process takes a long time and difficulty in finding data. The solution to solve is develop an activity recognition features. Development is carried out using the scrum method containing stages of user story, product backlog, sprint planning, daily scrum, sprint review, and sprint retrospective. The features produced are according to needs.